Azeroside C: a new phloroacetophenone glycoside from the roots of Dorema glabrum Fisch. & C.A. Mey - M.R. Delnavazi*; N. Yassa; A. Hadjiakhoondi; A. Delazar (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Dorema glabrum Fisch. & C.A. Meyfrom Umbelliferae family is a monocarpic species distributed in north-west of Iran, Azerbaijan republic and Armenia. The gum-resin of this species is traditionally used for the treatment of bronchitis, catarrh and diarrhea, as well as for its diuretic properties. Recently, we have reported the isolation of five phloroacetophenone glycosides including echisoside, pleoside, hyrcanoside, azerosides A and B from the roots of D. glabrum. The work is a part of our ongoing research on phytochemical constituents of this medicinal plant. Methods: The air dried and ground roots of D. glabrum collected from Jolfa region (East-Azerbaijan, Iran) was macerated, successively with n-hexane, chloroform, ethyl acetate and methanol-water (8:2). The hydroalcoholic extract was subjected to phytochemical analysis using Sephadex-LH20 and RP-18 column chromatography. Structure of the isolated compound was elucidated by 1H-NMR, 13C-NMR, HMBC, HSQC, EI-MS and CHNS elemental analysis. Results: A new structure of 2-O-[β-D-glucopyranosyl-(1''→3')-β-D-glucopyranosyl]-4-O-methyl-phloroacetophenone, which was named azeroside C, was isolated and identified from D. glabrum roots. Conclusion: The presence of new phloroacetophenone glycosides in D. glabrum highlights this species as a source of this group of natural products which can be used for further pharmacological and toxicological studies.